Management of Lifestyle Disorders with Tenets of Ayurveda - Kumar Bhaskar; Kiran Kumari; Rohit Ranjan; V. S. Pandey (AYUSHDHARA, 2022)
Ayurveda is one of the world’s ancient health care systems. Ayurveda has always emphasized maintaining the health and prevention of diseases by following a proper diet and lifestyle regimen rather than treatment and cure of the diseases. Ayurveda describes Traya-upastambhah, three pillars for a healthy life are Aahar (proper diet), Nidra (proper sleep), and Brahmacharya (celibacy). Aahar has been given prime importance since the Vedic Period. It is considered Brahma in Upanishad. Acharaya Kashyapa gives it the name “Mahabhaisajya”. Lifestyle disorders originate due to Poor lifestyle which includes poor diet, poor eating habits, Viruddhahara (dietetic incompatibility), lack of exercise, Smoking, excess alcohol, poor sleep, stress due to heavy workload, and increased consumption of unhealthy food. So, nowadays the number of individuals having lifestyle diseases like Heart disease, Obesity, Diabetes, Hypertension, and Cancer are continuously increasing and these are the primary cause of death. According to WHO, four main types of lifestyle disorders are Cardiovascular disease, Cancer, Chronic respiratory diseases, and Diabetes. Diseases of infective origin can be easily treated as compared to lifestyle disorders because lifestyle disorders are generally non-reversible. It is the need of time to review the Ayurveda in order to apply measures in preventing the upcoming epidemic of lifestyle disorders which are preventable with changes in diet (ahara), lifestyle, and environment.